1981
DOI: 10.1071/ch9810247
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of lead dioxide electrodes in acidic sulfate electrolytes

Abstract: The variation of discharge capacity during charge-discharge cycling of a PbO, electrode, prepared by pressing PbO, powder onto a smooth lead disc, in sulfuric acid and acidic ammonium sulfate solutions of various concentrations was investigated by the potentiodynamic technique. The discharge capacity was found to increase with cycle number in 0.05-4.3 rnol dm-3 H2S04; this was explained in terms of the increase in porosity of the electrode with cycling. The rate of increase was highest in a 1 rnol dmM3 solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In addition many experiments were carried out in different concentration of H 2 SO 4 (5, 1 and 0.5 M) which are in agreement with previous reports [24,25]. These results could be summarized as follows:…”
Section: Electrochemical Behavior Of Lead In H 2 So 4 Solutionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition many experiments were carried out in different concentration of H 2 SO 4 (5, 1 and 0.5 M) which are in agreement with previous reports [24,25]. These results could be summarized as follows:…”
Section: Electrochemical Behavior Of Lead In H 2 So 4 Solutionsupporting
confidence: 90%
“…Electrochemical behavior of lead in alkaline and acidic condition has been widely studied because of its high application [24][25][26]. Three potential regions according to the crystal structure and the chemical composition of the anodic layer in H 2 SO 4 can be recognized [27,28]: There is an anodic peak that corresponds to the oxidation of Pb to PbSO 4 .…”
Section: Electrochemical Behavior Of Lead In H 2 So 4 Solutionmentioning
confidence: 99%
“…These and other studies have suggested mechanisms for the incorporation of hydrogen either into the crystal structure of PbO2 itself (7,8,14,(19)(20)(21), or onto the surfaces of the PbO2 particles (9, i0, Ii, 14,22), and for the possible role of hydrogen atoms in the battery charge/discharge processes (23)(24)(25). Furthermore, recent studies (15,(26)(27)(28)(29) have corroborated earlier, largely ignored, work (30) that suggested that chemical PbO~ may not be electrochemically inactive after all. Furthermore, recent studies (15,(26)(27)(28)(29) have corroborated earlier, largely ignored, work (30) that suggested that chemical PbO~ may not be electrochemically inactive after all.…”
mentioning
confidence: 90%
“…In the present study we have used the novel electrolyte consisted of 1.1 M sulfuric acid and 0.5 M ammonium sulfate which has good buffer capacity and benefits to PbO 2 electrode [8].…”
Section: Introductionmentioning
confidence: 99%